PHENOMENOLOGY OF CRIMINALITY THROUGH CRIMINOTEOLOGICAL AND SPIRITUAL-VALUE (CULTURAL) PARADIGM: DIALOGICAL REPRESENTATION (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to the study of the phenomenology of crime through the criminological and spiritual-value (cultural) paradigm using the method of dialogical representation. The phenomenology of crime, being one of the aspects of the general phenomenology of society, is at the same time a study of the forms of manifestation of crime. The method of dialogic representation, which we indicated in the title of the article, consists in reproducing the Socratic method of questioning, in the apparent, ideal modeling of the researcher's dialogue, by asking interrelated questions and providing coherent answers. This is a kind of intellectual performance, an existential experiment. As a result of its application, a special idea of the nature of crime and tasks in the field of combating its reproduction was formed.
Keywords: crime; phenomenology; criminology; spirit; values; dialogue; dialogic representation; combating crime